Impact of COVID-19 pandemic on childhood immunization in a Tertiary Health-Care Center - Afreen Khan; Aparna Chakravarty; Jagannath Mahapatra (Wolters Kluwer Medknow Publications, 2021)
Background: After the emergence of COVID-19 pandemic, health facilities nationwide became the battleground for COVID-19. Many hospitals are designated as COVID-19 hospitals and various measures taken by the government to contain the spread of infection have disrupted the provision of routine health-care services including immunization. The aim of this study is to describe the impact of COVID-19 pandemic on immunization in a tertiary level health-care facility. Materials and Methodology: Data of children vaccinated as per the Universal immunization program (UIP) schedule were retrieved from immunizations records for a 7 month (January to July) period for the years 2019 and 2020. The trends of vaccination during COVID-19 pandemic are studied and are compared with the date matched data of the previous year. Results: There was a significant drop in the vaccine counts after emergence of COVID-19 pandemic. Maximum drop (−87%) was seen during the month of April (76.52% ± 43.62% vs. 16.95% ± 42.55%; P < 0.001) followed by May and June when it was −67% and −33%, respectively. Conclusion: COVID-19 pandemic has created the gaps in immunization which requires immediate attention. Further failure in sustaining the vaccination services and weak catch-up plans can lead to the emergence of vaccine-preventable diseases which may result in increased childhood morbidity and mortality.